Degradation of Some Antibiotics in Aqueous Solution Using UV/ZnO Process - Chaudhuri, M.; Emad, E.
Antibiotics are emerging contaminants in the aquatic environment because of their adverse effects on aquatic life and humans. The study examined the effect of operating conditions (zinc oxide concentration, pH and reaction time) of UV/ZnO on degradation of amoxicillin, ampicillin, cloxacillin in aqueous solution. The UV/ZnO photocatalysis is more effective for degradation of cloxacillin compared to ampicillin and amoxicillin degradation. pH has a great effect on amoxicillin , ampicillin and cloxacillin degradation. Complete degradation of all studied antibiotics was achieved at basic condition. The optimum operating conditions for degradation of antibiotics aqueous solution were observed to be ZnO concentration 0.5 g/L, pH 11 and irradiation time 180 min. Under optimum operating conditions, complete degradation of amoxicillin, ampicillin, cloxacillin. Finally, UV/ZnO photocatalysis can be used as a pretreatment process for amoxicillin, ampicillin, and cloxacillin degradation.